2015
DOI: 10.1371/journal.pone.0126704
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of Glucose Lowering Effect of Metformin and Acarbose in Type 2 Diabetes Mellitus: A Meta-Analysis

Abstract: BackgroundMetformin is the first-line oral hypoglycemic agent for type 2 diabetes mellitus recommended by international guidelines. However, little information exists comparing it with acarbose which is also commonly used in China. This study expanded knowledge by combining direct and indirect evidence to ascertain the glucose lowering effects of both drugs.MethodsPubMed (1980- December 2013) and China National Knowledge Infrastructure databases (1994-January 2014) were systematically searched for eligible ran… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
29
0
4

Year Published

2016
2016
2021
2021

Publication Types

Select...
7
2
1

Relationship

1
9

Authors

Journals

citations
Cited by 50 publications
(33 citation statements)
references
References 66 publications
0
29
0
4
Order By: Relevance
“…ACA has been used clinically to prevent postprandial hyperglycemia for many years, and has been used to treat patients with T2DM or glucose intolerance [35]. Similarly to metformin, ACA has beneficial effects on body weight, onset of diabetes and cardiovascular risk [36,37]. In mice, ACA effect replicates some aspects of diet or caloric restriction associated with increased lifespan [38][39][40][41], and with inhibition of age-associated hypothalamic inflammation in a sex-specific manner [42].…”
Section: Introductionmentioning
confidence: 99%
“…ACA has been used clinically to prevent postprandial hyperglycemia for many years, and has been used to treat patients with T2DM or glucose intolerance [35]. Similarly to metformin, ACA has beneficial effects on body weight, onset of diabetes and cardiovascular risk [36,37]. In mice, ACA effect replicates some aspects of diet or caloric restriction associated with increased lifespan [38][39][40][41], and with inhibition of age-associated hypothalamic inflammation in a sex-specific manner [42].…”
Section: Introductionmentioning
confidence: 99%
“…The α-glucosidase inhibitor is responsible for the degradation of carbohydrates, it slows down the degradation of carbohydrates by inhibiting the activity of α-glucosidase competitively, so postprandial blood glucose level can be decreased and the postprandial blood glucose level comes under control. α-glucosidase inhibitors can be an alternative first line agent and provide several benefits, 3 it has been recommended by American Association of Clinical Endocrinologists and Third Asia-Pacific Region Diabetes Treatment Guidelines as the first-line of treatment for lowering postprandial hyperglycemia. Their efficacy in lowering HbA1c, and reducing post-meal blood sugars, make them suitable for use in type 2 diabetes.…”
Section: Introductionmentioning
confidence: 99%
“…Reduction of at least 0.5% is recommended for treating T2DM (15). Various studies on both dapagliflozin and canagliflozin have shown a reduction of Hba1c of 0.8% when compared to both placebos and active comparators (16,17,18,19,20).…”
Section: Sample Size Calculationmentioning
confidence: 99%